An Analysis of Training Programs and Their Impact on Teacher Productivity - Hery Wihasnanto (Journal of Islamic Studies & Social Science, 2025)
This study aims to analyze the impact of teacher training programs on improving teacher productivity. The research employed a qualitative descriptive approach conducted at a private educational institution in Bekasi. Data were collected through in-depth interviews, classroom observations, and document analysis involving eight teachers, the principal, and the vice principal for curriculum affairs.The findings indicate that training programs positively contribute to teacher productivity, particularly in improving pedagogical skills, lesson planning, the implementation of active learning methods, and the use of digital media in classroom instruction. Most teachers demonstrated improved ability in designing lesson plans and applying student-centered learning approaches. Additionally, training increased teachers’ confidence and work motivation.However, the effectiveness of the training programs has not been fully optimized due to limited reflective practices, insufficient follow-up supervision, and the absence of systematic professional discussion forums among teachers. The study concludes that teacher training programs will have a more sustainable impact when integrated with reflective practices, continuous supervision, and institutional support systems.